PERSEPSI KENYAMANAN DAN HARGA TERHADAP MINAT PENGGUNAAN JASA TRANSPORTASI ANGKUTAN UMUM KOTA DI KABUPATEN PURWAKARTA - Ade Nurhayati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
Reduced interest in the use of city public transport services because there are still many public transport facilities that do not attach importance to the convenience of service users and the absence of alternative tariff options for long distance or short distance, so service users choose to use other transportation services that can answer their needs, such as transportation online that already exists in Purwakarta today. In this case the author is very interested in conducting research, with the title